Upaya Meningkatkan Motivasi Belajar Peserta Didik melalui Media Pembelajaran Komik dalam Pembelajaran Pjok - Jojo’ Kholistyono Ngudinur Muhammad; Nanik Indahwati; Demy Ilmiawan (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
This research uses the Classroom Action Research (CAR) method with a cyclical approach to increase student learning motivation in Physical Education, Sports and Health (PJOK) subjects. This research was conducted in two cycles, each consisting of planning, implementation, observation and reflection stages. In Cycle I, the average student learning motivation was 44.05%, while in Cycle II it increased significantly to 74.68%, with an increase of 30.63%. This increase shows positive changes in students' interest and enthusiasm for learning. The research results showed that the use of "comic media" during learning in Cycle II was effective in stimulating students' interest and motivation. This increase in motivation also indicates the success of the emphasis on more interesting and participatory learning. These findings illustrate the positive impact of the improvement efforts made in Cycle II in creating a better learning environment. This research provides a positive view regarding the use of the PTK method with a cycle approach and the implementation of "comic media" in increasing students' learning motivation in PJOK subjects. The implications of these findings emphasize the importance of innovative approaches to learning to achieve more optimal results.